2010
DOI: 10.1038/eye.2010.137
|View full text |Cite
|
Sign up to set email alerts
|

Comparation of the new rebound tonometer IOPen and the Goldmann tonometer, and their relationship to corneal properties

Abstract: Purpose To compare the intraocular pressures (IOPs) obtained with the IOPen rebound tonometer, Goldmann applanation tonometer (GAT) and the ocular response analyzer (ORA) and investigate the effects of corneal biomechanical properties on IOPen measurements. Methods A total of 198 normal eyes were included in this cross-sectional and randomized study. Three measurements were taken using IOPen. Agreement between tonometers was calculated using the Bland and Altman limits of agreement (LoA) analysis. Results The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
0
10
0
5
Order By: Relevance
“…[16][17][18] However, it is worthwhile mentioning the recent reports made by Rosentreter and colleagues, 19,20 who claim that the conventional Icare tonometer underestimates significant IOP comparing to GAT, in patients with a corneal abnormality such as those who have undergone keratoplasty, as rebound tonometry may be extremely affected by corneal properties. 21,22 There is scarce information in the relevant literature regarding the correlation existing between rebound and Perkins when used in pediatric patients. In this subset of patients, Martı´nez-de-la-Casa et al 2 detected good correlation using the conventional Icare in children aged 3 to 13 who were cooperative enough to avoid general anesthesia (r = 0.869, P < 0.001).…”
Section: Discussionmentioning
confidence: 98%
“…[16][17][18] However, it is worthwhile mentioning the recent reports made by Rosentreter and colleagues, 19,20 who claim that the conventional Icare tonometer underestimates significant IOP comparing to GAT, in patients with a corneal abnormality such as those who have undergone keratoplasty, as rebound tonometry may be extremely affected by corneal properties. 21,22 There is scarce information in the relevant literature regarding the correlation existing between rebound and Perkins when used in pediatric patients. In this subset of patients, Martı´nez-de-la-Casa et al 2 detected good correlation using the conventional Icare in children aged 3 to 13 who were cooperative enough to avoid general anesthesia (r = 0.869, P < 0.001).…”
Section: Discussionmentioning
confidence: 98%
“…In the future, it may be important to study the effects of other corneal properties, such as curvature, elasticity, and rigidity on RT-based mouse IOP measurements (Moreno-Montanes et al, 2011), as these properties are not reflected in simple CCT measurement (Munger et al, 2001) and may also have an impact on probe head deceleration times. Additionally, studying mice at older ages may be needed as some have reported that CCT may not be fully matured until 7–8 weeks for C57BL/6 mice (Burns et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous recent studies have compared RT with GAT 11,12 . Most have utilized the RT manufactured by iCare (iCare, Helsinki, Finland).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 198 normal eyes, Moreno‐Montanes et al 11 . reported on another type of RT, the IOPen (Medicel, Wolfhalden, Switzerland).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation